Literacy and initial reading instruction in the teaching practices of a teacher participating in PNAIC – Early Childhood Education - Silva, Maria da Conceição Lira da (2021)
This article sought to analyze reading and writing teaching practices developed by an Early Childhood Education teacher who participated in the continuing education course of the National Pact for Initial Reading Instruction at the Right Age (PNAIC). The research adopted a qualitative approach, and had as its empirical field a Center for Early Childhood Education. The methodological procedures consisted in observations, interviews and exploratory analysis of the collection covered in the course. The data analysis, based on thematic content analysis, revealed that the teacher contemplated the two facets of the written language –literacy and initial reading instruction. We noticed the use of some elements of the PNAIC formation, such as the investment in reading literacy and the phonological analysis of words.